2004
DOI: 10.1021/ic048736a
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Quinolinates:  Infrared-Emitting Molecular Materials with a Rich Structural Chemistry

Abstract: Near-infrared-emitting rare-earth chelates based on 8-hydroxyquinoline have appeared frequently in recent literature, because they are promising candidates for active components in near-infrared-luminescent optical devices, such as optical amplifiers, organic light-emitting diodes, .... Unfortunately, the absence of a full structural investigation of these rare-earth quinolinates is hampering the further development of rare-earth quinolinate based materials, because the luminescence output cannot be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 48 publications
(93 reference statements)
6
78
0
Order By: Relevance
“…We have performed this analysis in Er-quinoline complexes, for which detailed x-ray studies have been reported. 7,13 The comparative study confirms that Eq. ͑4͒ just leads to a negligible underestimation, ϳ10%, of the exact dipole-induced transfer rate, calculated using Eq.…”
Section: ͑2͒supporting
confidence: 75%
See 2 more Smart Citations
“…We have performed this analysis in Er-quinoline complexes, for which detailed x-ray studies have been reported. 7,13 The comparative study confirms that Eq. ͑4͒ just leads to a negligible underestimation, ϳ10%, of the exact dipole-induced transfer rate, calculated using Eq.…”
Section: ͑2͒supporting
confidence: 75%
“…A further elegant proof of this scaling law is provided by Van Deun's experimental results in solutions of complexes synthesized with the same mononuclear molecular structure, namely, Er-8-quinoline ͑ErQ͒, Er-5-chloro-Q ͑Er5ClQ͒, and Er-5,7-dichloro-Q ͑Er57ClQ͒. 7 In these systems, the Cl contribution to ͗␣ A ͘ Er is negligible, owing to the heavy mass of the halogen atom. 6 Neglecting the contribution of the solvent, ͗␣ A ͘ Er is proportional to the density of CH groups, and, hence, to the number N H of hydrogen per each quinoline.…”
Section: ͑2͒mentioning
confidence: 91%
See 1 more Smart Citation
“…1 show an absorption peak centered at 380 nm, corresponding to one of the → * absorption transitions of the quinoline ligand. 21,28,29 Comparing these spectra to the ones related to ErQ 3 evaporated thin films and ErQ 3 solution, a similar behavior can be observed, suggesting that the light sensitization scheme of the material is preserved by HTSC deposition. Laser-induced photoluminescence ͑PL͒ spectra of spincoated thin films ͑see Fig.…”
supporting
confidence: 55%
“…A possible strategy to overcome such drawback is the substitution of the H atoms with heavier halogen atoms in the ligands. Successful examples showing the improvement of the NIR light emission have been reported in the literature [1][2][3].…”
Section: Introductionmentioning
confidence: 99%